2011
DOI: 10.1017/s0007114511006015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of soya oligosaccharides and soya oligopeptides on lipid metabolism in hyperlipidaemic rats

Abstract: In the present study, we aimed to examine the effects of soya oligosaccharides (SOS) and soya oligopeptides (SOP) on blood lipid levels, release of vasoactive substances, antioxidant activity and faecal bile acid (FBA) excretion in rats fed a high-fat diet (HFD). Male SpragueDawley rats were evenly divided into five groups according to diets as follows: regular diet (control), HFD, HFD enriched with 2 % of SOS (SOS), HFD enriched with 3 % of SOP (SOP) and HFD enriched with 2 % SOS and 3 % SOP (SOSP). The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 45 publications
1
5
0
1
Order By: Relevance
“…Cardiovascular disease (CVD) is the leading cause of mortality in the world and hypercholesterolemia is recognized as a major independent risk factor in CVD (1). Maintaining cholesterol levels in the normal range can help prevent the initiation and progression of CVD.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular disease (CVD) is the leading cause of mortality in the world and hypercholesterolemia is recognized as a major independent risk factor in CVD (1). Maintaining cholesterol levels in the normal range can help prevent the initiation and progression of CVD.…”
Section: Introductionmentioning
confidence: 99%
“…Although a previous study demonstrated that supplemental feeding with epilactose did not have an impact on the plasma lipid concentration in rats fed high-sucrose diets ( 20 ) , some prebiotic oligosaccharides reportedly exhibit an ameliorative effect on diet-induced obesity and metabolic dysregulation ( 9 , 21 , 22 ) . The present study showed that epilactose effectively prevents metabolic disorders probably through the up-regulation of UCP-1 expression in skeletal muscles and brown adipose tissue in mice fed HF diets.…”
Section: Discussionmentioning
confidence: 98%
“…singuonensis . The cholesterol‐lowering action of phytic acid (Jariwalla, 1999; Lee et al , 2005 b ), stachyose (Xie & Shi, 2006; Lan et al , 2007) and soy isoflavones (Kawakami et al , 2005; Mezei et al , 2006), however, has been well documented in terrestrial animals. These results appear to indicate either that cholesterol metabolism in fishes is different from that of terrestrial animals or that there is a multiplicity of mechanism involved in the control of cholesterolaemia in fishes (Kaushik et al , 1995; Dias et al , 2005), which needs further study.…”
Section: Discussionmentioning
confidence: 99%